The role of muscle forces and gait cycle discretization when assessing acetabular cup primary stability: A finite element study. (March 2023) - Fallahnezhad, Khosro; O'Rourke, Dermot; Bahl, Jasvir S.; Thewlis, Dominic; Taylor, Mark
Highlights: A patient specific FE model of the hemipelvis was developed. The influences of the muscle force contribution and loading cycle discretization on the predicted micromotion and interfacial bone strains were investigated. The acetabular cup micromotion and interfacial bone strains can be predicted just using the joint contact force. The gait cycle needs to be adequately discretised to capture the micromotion at the bone-implant interface. Abstract: The aim of this study was to investigate the influence of the muscle force contribution and loading cycle discretization on the predicted micromotion and interfacial bone strains in the implanted acetabulum. To this end, a patient specific finite element model of the hemipelvis was developed, based on the CT-scan and gait analysis results, collected as part of the authors' previous work. Outcomes of this study suggests that the acetabular cup micromotion and interfacial bone strains can be predicted just using the joint contact force. This helps to reduce the complexity of the finite element models by ignoring the contribution of muscle forces and the associated challenges of mapping these forces to the pelvis. However, the gait cycle needs to be adequately discretised to capture the micromotion at the bone-implant interface. Background and Objective: The Dalstra load case, which includes muscle forces, has been widely adopted in the literature for studying the mechanical environment in the intact and implanted acetabulum. To simplify the modelling approach, some researchers ignore the contribution of muscle forces. The Dalstra load case is also divided into eight separate load steps (five in the stance phase and three in the swing phase), however, it is unclear whether this adequately captures the micromotions, for a cementless acetabular cup, during a simulated activity. The aim of this study was to investigate the influence of the muscle force contribution and loading cycle discretization on the predicted micromotion and interfacial bone strains. Methods: In this work, a patient specific finite element model of the hemipelvis was developed, based on the CT-scan and gait analysis results, collected as part of the authors' previous work. Finite element simulations were performed using the joint contact and muscle forces derived from two sources. The first approach was used the load case proposed by Dalstra et al. The second approach used joint contact and muscle forces predicted by a musculoskeletal model. Additionally, the musculoskeletal load case was discretised into 50 equal load steps and the results compared with the equivalent Dalstra load steps. Results: The results showed that the contribution of the muscle forces resulted in minor differences in both the magnitude and distribution of the predicted acetabular micromotion (up to 4.01% in the mean acetabular micromotion) and interfacial bone strains (up to 10.34% in the mean interfacial bone strains). The degree of gait cycle discretisation had a significant influence on the acetabular micromotion with a difference of 20.89% in the mean acetabular micromotion. Conclusion: Outcomes of this study suggests that the acetabular cup micromotion and interfacial bone strains can be predicted just using the joint contact force. This helps to reduce the complexity of the finite element models by ignoring the contribution of muscle forces and the associated challenges of mapping these forces to the pelvis. However, the gait cycle needs to be adequately discretised to capture the micromotion at the bone-implant interface.